When is enough, enough? And what should the criminologist say? - Christie Nils (Temida, 2003)
In this paper, the author is trying to find the answers to questions when is enough, enough, and what is the role of the criminologists in the process of establishing the balance between the crime control carried out by the state and the civil society and its basic values. Each state can be evaluated by its penal system that reflects the crucial centers of the state control and power, conveying at the same time information about the way we are not supposed to go. Namely, the penalty, which means the infliction of pain against the accused, presents the negation of the basic ethical, moral human, civilized principles. In that way, the penalty becomes a dangerous for the society, as well as the serious obstacle for ideals of the social cohesion and assimilation. He is showing that on the examples of penal systems in several countries, such as Finland, Russia, Byelorussia and Norway, giving a critical overview of the penal system of the USA. The USA penal system is a good example of breaking off the links with the basic societal values, representing at the same time crime against people in the USA, as well as in other (European) countries due to the strong influence which the States have in this domain because of their economy power on the global plan. Bearing that in mind, the author is concluding that the criminologists should begin the analysis from another point of view: not from the offender and the criminal offence, but from the existing penal system in order to find out what kind of pain and what way of its causing would be acceptable in the certain historical, societal, and cultural context; in other words how big the penal system should be, without endangering the basic values at the same time.